Natural Enemies of Terrestrial Molluscs 2004
DOI: 10.1079/9780851993195.0279
|View full text |Cite
|
Sign up to set email alerts
|

Predatory gastropods as natural enemies of terrestrial gastropods and other invertebrates.

Abstract: In this chapter, the occurrence of carnivory in terrestrial gastropods is surveyed, and the aggressive and cannibalistic behaviours in these animals are summarized. The evolution of carnivory as a feeding strategy and the associated morphological specializations are analysed. Finally, the lessons learnt from previous use of carnivorous species in biological control are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 0 publications
3
70
0
4
Order By: Relevance
“…The absence of land snail herbivory on elements of the large flora of herbaceous perennial plants is remarkable, but there is anyway a general spatial incongruence between habitat of these plants and that of most snails. The near absence of indigenous land snail in areas subject to anthropogenic disturbance (Barker, 2002) asserts to the dependence of the New Zealand fauna on retention of a humus layer buffered from the weather by vegetation cover. Nekola (2003) documented similar sensitivities in North American land snails.…”
Section: C L U D E D a R Et H Ee L L O B I I D A E (M A R I N El I mentioning
confidence: 99%
“…The absence of land snail herbivory on elements of the large flora of herbaceous perennial plants is remarkable, but there is anyway a general spatial incongruence between habitat of these plants and that of most snails. The near absence of indigenous land snail in areas subject to anthropogenic disturbance (Barker, 2002) asserts to the dependence of the New Zealand fauna on retention of a humus layer buffered from the weather by vegetation cover. Nekola (2003) documented similar sensitivities in North American land snails.…”
Section: C L U D E D a R Et H Ee L L O B I I D A E (M A R I N El I mentioning
confidence: 99%
“…It is unlikely that many gastropod will be found that can filfill these criteria. An extensive review of attempts to control pest molluscs using predatory gastropods can be found in Barker & Efford (2004).…”
Section: Resultsmentioning
confidence: 99%
“…The aperture shows a partial occlusion in its median region due to the palatal tooth and the columellar lamella. Apertural occlusions by strong structures such as seen in C. carvalhoi are typical barriers that protect against predators that attack through the aperture (Solem, 1972;Goodfriend, 1986;Stanley, 1988;Vermeij, 1993;Gittenberger, 1996;Barker & Efford, 2004).…”
Section: Cortana Carvalhoi (Brito 1967) Comb Nov (Figs 40-42)mentioning
confidence: 99%
“…As C. coelhoi has only the columellar lamella, it is plausible to suppose that, due to this fossil's old age, the lamella has been the first structure to appear in the genus' history; the other teeth and lamellae would have appeared later. The strong and raised lamella of C. coelhoi is a typical barrier to obstruct the aperture, protecting the animal against predators (Solem, 1972;Goodfriend, 1986;Stanley, 1988;Vermeij, 1993;Gittenberger, 1996;Barker & Efford, 2004 Geographic and stratigraphic occurrence: With this record, the species is also known from the limestones of Itaboraí Basin. The precise stratigraphic occurrence can't be assessed; probably Sequence S1, the same sequence of occurrence of the other orthalicids (Medeiros & Bergqvist, 1999;Bergqvist et al 2006).…”
Section: Examined Material: Typesmentioning
confidence: 99%
See 1 more Smart Citation